2019
DOI: 10.1007/s10452-019-09679-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential resource consumption in leaf litter mixtures by native and non-native amphipods

Abstract: Leaf litter processing is an essential ecosystem function in freshwater systems, since much of the carbon and nutrients moving through freshwater food webs come from the surrounding terrestrial ecosystems. Thus, it is important to understand how the species performing this function differ, especially because many native species are being replaced by non-native species in aquatic ecosystems. We used a field experiment to examine leaf consumption rates of two common shredding macroinvertebrates (the native Gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Results from the hierarchical clustering indicated that NLFA were derived mainly from FPOM in G. pulex under both light and dark conditions. The lack of effect on their survival rates and NLFA concentrations is related to their ability to meet their basic metabolic needs by ingesting leaf debris from good quality litter such as alder leaves (Little & Altermatt, 2019). However, we suggest that only the occurrence of microalgae colonising FPOM can explain the better growth rate observed in light‐reared G. pulex .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the hierarchical clustering indicated that NLFA were derived mainly from FPOM in G. pulex under both light and dark conditions. The lack of effect on their survival rates and NLFA concentrations is related to their ability to meet their basic metabolic needs by ingesting leaf debris from good quality litter such as alder leaves (Little & Altermatt, 2019). However, we suggest that only the occurrence of microalgae colonising FPOM can explain the better growth rate observed in light‐reared G. pulex .…”
Section: Discussionmentioning
confidence: 99%
“…For G. pulex , our experiment showed that detrital food sources remain quantitatively important in terms of supply of C and sterols. This might be even more important when fine particles come from tree species known for the palatability of their leaf litter (Little & Altermatt, 2019). Microalgae collected in biofilm and/or with FPOM usually have been considered as a minor complementary food, but here they appear to be of paramount nutritional importance to meet a large part of the LC PUFA needs of amphipods.…”
Section: Discussionmentioning
confidence: 99%
“…Blue-green links have been increasingly recognised in sustaining vital ecosystem processes. For example, terrestrial organic carbon can be an important diet component for lake plankton (Cole et al, 2011), many aquatic invertebrates feed on terrestrial input in the form of leaf litter (Little & Altermatt, 2019), and fish can rely on terrestrial prey (Sato et al, 2011). In addition, emerging aquatic insects are an important food source for a wide variety of terrestrial predators, including birds (Twining et al, 2018), bats (Fukui et al, 2006), beetles and spiders (Paetzold et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on their Functional Feeding Group (FFG), limited access to long-chain diatom PUFAs from biofilms is likely to have a contrasting effects among different consumers. The fitness of grazers such as members of the family Heptageniidae, which derive the majority of their carbon from microalgae (Ku ¨hmayer et al, 2020), is highly dependent on the quality of their diet at the last larval instars (Winkelmann & Koop, 2007), whereas for a shredder such as Gammarus pulex (Linnaeus, 1758), the effect is more limited as it depends primarily on the quality of the leaf litter (Little & Altermatt, 2019). In this context, the resumption of autochtonous primary production in early spring could reduce the ecological constraints of limited access to long-chain PUFAs, as the amount of accessible epilithic biofilm is known to have a positive effect on consumer growth at this time (Hill et al, 2010).…”
Section: Introductionmentioning
confidence: 99%